1993
DOI: 10.1161/01.cir.88.5.2267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inotropic stimulation on the negative force-frequency relationship in the failing human heart.

Abstract: Background. In severe human heart failure, an increase in frequency of stimulation is accompanied by a reduced force of contraction in vivo and in vitro. The present study was aimed to investigate whether inotropic stimulation influences the inverse force-frequency relationship in failing human myocardium.Methods and Results. The effects of the cAMP-independent positive inotropic agents ouabain (0.01 ,imol/L) and BDF 9148 (0.1 ,umol/L) as well as the 3-adrenoceptor agonist isoprenaline (0.01 ,umol/L

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(49 citation statements)
references
References 28 publications
7
41
0
1
Order By: Relevance
“…Schwinger et al 35 demonstrated partial reversal of the negative forcefrequency relationship in failing human myocardium with low-dose isoprenaline, and similar in vitro effects have been observed with gene transfer of sarcoplasmic reticulum calcium ATPase. 36 Myocyte "recovery" after mechanical circulatory support is also associated with improved forcefrequency.…”
Section: Force-frequency and Relaxation-frequency Relationshipsmentioning
confidence: 61%
“…Schwinger et al 35 demonstrated partial reversal of the negative forcefrequency relationship in failing human myocardium with low-dose isoprenaline, and similar in vitro effects have been observed with gene transfer of sarcoplasmic reticulum calcium ATPase. 36 Myocyte "recovery" after mechanical circulatory support is also associated with improved forcefrequency.…”
Section: Force-frequency and Relaxation-frequency Relationshipsmentioning
confidence: 61%
“…Measurements of active tension in these preparations consistently showed that the HCM muscle displays a positive force-frequency relationship (Figure 5A and 5B), in contrast to failing human myocardium 21 or end-stage human HCM. 22 In addition, muscle contractile reserve was preserved, as indicated by the positive inotropic response to isoproterenol.…”
Section: Contractile Function Of Hcm Trabeculae: I Nal Inhibition Impmentioning
confidence: 71%
“…Experiments were performed as described in detail previously (30). Immediately after excision, the atrial muscle strips and ventricular papillary muscle strips were placed in ice-cold, preaerated Tyrode's solution and delivered to the laboratory within 10 min.…”
Section: Methodsmentioning
confidence: 99%